KEPERCAYAAN DALAM MASYARAKAT ISLAM ACEH - Ridwan Muhammad Hasan (Lembaga Sepercenter, 2026)
This study wants to lift and to determine the extent of the element animisms confidence and dynamism, in the Islamic community in Aceh, from their daily practice and so as to provide an overview and fanatical form of the customs, traditions and culture of Hinduism. As if, they believe and assume that on the big stump, banyan tree and trees, as well as objects that can be believed to have supernatural animism and dynamism. So the results of research that has been carried out that the Islamic community in Aceh until today still cling to the dogma that has been left by the previous, in the form of heresy, superstition and superstition and has become a daily belief in which it is difficult to be abandoned and omitted. Although that brings the teaching is not from Islam, precisely indirect trust, can form in socializing everyday highly unethical so impressed negative.